Studies on the use of plant growth-promoting rhizobacteria and effective microorganisms in controlling white root disease of rubber - Ikram A; Hashim I (Journal of Rubber Research, 1998)
Plant growth-promoting rhizobacteria (PGPR) and effective microorganisms (EM) were tested for biological control of white root disease of rubber caused by Rigidoporus lignosus. In laboratory agar-plate interaction studies, specific PGPR strains and EM antagonised growth of R. lignosus as well as two other root disease fungi, Ganoderma philippi and Phellinus noxious. The PGPR strain 7NSK2 and EM were then used to treat rubber seedlings in separate field experiments on an Entisol. The treatments were PGPR (or EM), triadimefon, triadimefon and PGPR (or EM) and an uninoculated control, in five replications. Plants, diseased or dead, were verified weekly for up to 24 (PGPR experiments) and 40 (EM experiments) weeks. Application of PGPR or EM did not suppress the disease, and their integration with triadimefon were no better than control by the fungicide alone.
Keywords: Disease control; Plant growth; Rhizobacteria; White root disease